The Behring Sea controversy [electronic resource] - Butler, Benj. F. (Benjamin Franklin), 1818-1893.; Argyll, John Douglas Sutherland Campbell, Duke of, 1845-1914. ([S.l. : s.n., 1892)
From: The North American Review, vol. 154, no. 426. Caption title. Electronic reproduction. Mode of access: Internet. 44